Impact of Secondary Alveolar Bone Grafting on the Symptoms of Reflux in Oronasal Fistulas: A Patient-Related Outcome Study. (May 2014) - Pepper, Hannah B.; Revington, Peter J.; Deacon, Scott; Thomas, Steve
Objective: To establish for the first time the prevalence of fistula symptoms and the effectiveness of secondary alveolar bone grafting to treat these symptoms in a single surgeon cohort in Bristol, United Kingdom. Design: Direct questioning of 233 consecutive patients with cleft before and after secondary alveolar bone grafting as to the presence of fistula symptoms. Setting: Southwest and South Wales Cleft Centre, Frenchay Hospital, Bristol, United Kingdom. Participants: Consecutive patients with cleft who were being treated for secondary alveolar bone grafting. Outcome Measure: Patients reporting presence of fistula symptoms. Data collection on cleft type (unilateral, bilateral), date of birth, and age at secondary alveolar bone grafting. Results: Of the 167 unilateral patients with cleft lip and palate and 66 patients with bilateral cleft lip and palate, 45% had symptoms of a fistula before alveolar bone grafting and 10% had symptoms of a fistula after surgery. There were no statistically significant differences between the presence of symptoms before or after secondary alveolar bone grafting between cleft types or by age at secondary alveolar bone grafting. Conclusion: This is the first study examining the rates of fistula symptoms before and after secondary alveolar bone grafting in the United Kingdom. This study used the patient-centered outcome of the presence of symptoms as a way of measuring the presence of fistulas in this group. Secondary alveolar bone grafting reduces the incidence of symptomatic fistula in this setting.